Screening gender in Moroccan Cinema: Endorsing or combating gender stereotypes - Hafssa Chahbane; Khalid Houssaini (Social Sciences and Humanities Open)
Using a qualitative approach, this study seeks to understand the way gender is depicted in Moroccan movies through the lens of both male and female filmmakers. Given the media's powerful influence in shaping societal and cultural norms, this research delves into the portrayal of gender stereotypes in Moroccan movies, a topic that has received little attention thus far. Through content analysis of four influential Moroccan drama movies, this study attempts to systematically examine both visual and verbal components. The results indicate that the majority of the analyzed movies reinforce gender roles and stereotypes through both their cinematography and screenplay. Additionally, the study highlights the fact that compared to her male counterpart, the female director is more inclined to incorporate gendered messages and challenge the cultural norms, working to subvert some of the most common gender stereotypes by highlighting women's suffering, inferiority, and victimization.